Niemann Pick Disease: A Case Report - Bari, Md Iqbal; Haque, M Imdadul; Siddiqui, Abu Bakar; Hossain, M Asgar; Alam, T (TAJ: Journal of Teachers Association, 2011)
DOI: http://dx.doi.org/10.3329/taj.v15i1.8379 TAJ 2002; 15(1): 32-34